Implementasi Contextual Teaching and Learning (CTL) Berbasis Lingkungan Dalam Pembelajaran IPA di MIM Unggulan Kota Gorontalo - Rafika Alim; Yulanti S. Mooduto; Yane Hardiyanti Mahmud (Transbahasa, 2026)
This study aims to analyze the implementation of Environment-Based Contextual Teaching and Learning (CTL) in science learning at MIM Unggulan Kota Gorontalo. This research employed a qualitative approach with a case study design to gain an in-depth understanding of contextual learning processes. The research subjects consisted of the principal, science teachers of grades IV, V, and VI, and students. Data were collected through participatory observation, semi-structured interviews, and documentation. Data analysis was conducted using an interactive model, including data condensation, data display, and conclusion drawing. The findings reveal that the implementation of environment-based CTL has been carried out through seven main components: modeling, inquiry, questioning, learning community, constructivism, reflection, and authentic assessment. The learning process utilizes the surrounding environment as a learning resource, such as direct observation of plants and leaves, which encourages students’ active participation. This implementation positively impacts students’ conceptual understanding, learning engagement, and critical thinking skills. However, several challenges remain, including limited student participation in questioning activities and the need for strengthening teachers’ instructional strategies. In conclusion, environment-based CTL serves as an effective alternative approach to improving the quality of science learning processes and outcomes at the elementary school level. This study contributes to the development of contextual, innovative, and environment-based learning strategies.